The entrepreneur's toolkit - Goldsby, Michael G.; Teaching Company (Chantilly, Virginia : The Teaching Company, 2014)
All of us have dreams, goals, and perhaps a project or two on the back burner. The Entrepreneur's Toolkit is your chance to make these aspirations a reality. Professor Goldsby provides a detailed roadmap for starting, nurturing, expanding, and eventually selling a business; and he shows how the same valuable skills translate to other spheres of life.
Keywords: Entrepreneurship; New business enterprises; Small business